Expatriate training and support: How effective are multinational companies’ practices in Cyprus? - Hadjiyianni, Chara (2009)
Most of the literature demonstrates that multinational companies do not adequately train and support expatriates prior to and during overseas assignments. If expatriates do not sufficiently adjust to host-country conditions, this can have detrimental effects on expatriate managers themselves, the assignment and the sending organisation. This study examines the effectiveness of expatriate training and support practices of multinational companies in Cyprus. The dissertation builds on three themes which emerge from the literature: the challenges expatriates face in the host country, the types of expatriate training and support offered by companies and the effectiveness of these practices. The findings reveal that the main challenges in Cyprus include task difficulties, interaction with locals outside work and family adjustment. Organisational training policies were focused on work-specific issues and more often took place in Cyprus than in the parent country. However, cross-cultural training was limited. Support efforts were centred on financial assistance and tended to overlooked practical support and communication. Only one organisation (an NGO) provided wide-ranging support activities. Expatriates’ families were not included in training and support schemes. Overall, most training and support practices fell short of managers’ expectations. The research highlights the need for increased interactive job-specific training, language lessons, practical assistance, communication with the parent company and family support in Cyprus. The study also emphasises the importance of adopting a contingency approach to expatriate training and support. Factors to consider include assignment purpose, role novelty, family circumstances, degree of interaction with locals and differences between parent- and host-country living conditions. The findings suggest that organisational sector, international experience and management philosophy may influence companies’ approach to expatriate HR policies. Given that academic research on international HR practices in Cyprus is currently limited, this study contributes to an initial understanding of expatriate needs and company practices in the country. In contrast with prevalent literature which tends to focus on commercial organisations, this study broadens the research field by including an NGO alongside corporate firms.